Collier's junior classics - Matignioni, Margaret E., ed.; Livsey, Rosemary E., ed.; Gross, Elizabeth H., ed.; Gaver, Mary V., ed.; McGuire, Alice Brooks., ed.; Young, Marian C., ed. (New York : Crowell-Collier Pub, 1962)
Contents.--v.1. A, B, C., Go! / ed. R.E. Livsey.--v.2. Once upon a time / ed., E.H. Gross.--v.3. Magic in the air / ed., M.V. Gaver.--v.4. Just around the corner / ed., A.B. McGuire.--v.5. In your own backyard / ed., M.C. Young.--v.6. Harvest of holidays / ed., R.W. Stewart.--v.7. Legends of long ago / ed., J. Darrah.--v.8. Roads to greatness / ed., L. Galloway.--v.9. Call of adventure / ed., C. Rollins.--v.10. Gifts from the past / ed., E. Alexander.
Keywords: Children's literature (Collections)